NOVEL CONTROL STRATEGY FOR GRID-CONNECTED PHOTOVOLTAIC ARRAY - Noroozian, Reza; Gharehpetian, G. B. (IIUM Engineering Journal, 2016)
<span style="font-family: 'Times New Roman','serif'; font-size: 9pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-language: AR-SA; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-font-weight: bold;">In this paper, the configuration of the PV generation system, the dynamic model for PV modules and its power electronic interfacing have been presented. A novel control strategy for the DC-DC converter has been developed in order to extract the maximum amount of power from the PV array. Also, a novel control strategy, which is based on d-q rotating reference frame, has been proposed for the DC-AC converter. The simulation results, based on PSCAD/EMTDC, show that the novel control scheme can transfer the DC energy from PV array, compensate the power factor of AC grid and improve the dynamic behavior of grid-connected PV system.